Analysis of The Influence of Audit Committee, Sharia Supervisory Board, and Islamic Work Ethic on The Quality of Sharia Bank Financial Statements in Indonesia - Iwan Budiyono; Chansera Kista Sabilla (Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
Purpose - This study aims to analyze the influence of audit committees, sharia supervisory boards, and Islamic work ethic on the quality of islamic bank financial statements in Indonesia.Method - The method in this study used Multiple Linear Regression Analysis with SPSS software tools.Result - Based on the results of this research, simultaneously the audit committee, sharia supervisory board, and Islamic work ethic have a significant influence on the quality of islamic bank financial statements in Indonesia. Meanwhile, in part, the audit committee and islamic work ethic have no significant effect on the quality of islamic bank financial statements in Indonesia. SSB partially affects the quality of islamic bank financial statements in Indonesia.Implication - This study uses the data from Islamic bank financial statement in Indonesia, audit committees, sharia supervisory boards, Islamic work ethic.Originality - The data was taken with the dissemination of questionnaires distributed to 30 respondents. The respondents were a reflection of the members of the audit committee and SSB who were qualified as students of sharia banking polytechnic state of semarang who had received islamic bank audit courses.